Use of stereotypical social gender roles in an L2 narrative construal task by advanced, Polish learners of English - Badio, Janusz; Agnieszka Gralak (Focus on events and narratives in language, psychology, social and medical practice, 2020)
The article presents a study of the process of comprehension of an input joke and its subsequent retelling in writing by Polish advanced students (n=36) of English as a foreign language. The research question was whether people are guided by stereotypical social gender roles and cultural schemata during comprehension and production of a joke involving events that make up a story. The joke included references to female (wife) and male (husband) participants as well as a secretary (gender not specified), names Gloria and Mike and a number of objects such as: violets, chocolates, handbag or laptop. It was predicted that the VM version of the joke (the version with the name Mike, supposedly male secretary) would take the participants more time to interpret as compared to the VF version (with Gloria as a most possible candidate for the secretary role). This hypothesis was indeed confirmed, but the experimental subjects did not take significantly more time to write their versions (VM and VF conditions) of the story. The qualitative analysis demonstrated variable cultural bias during the construction of the participants’ roles and relations, often against or in the absence of clear instructions in the input to do so.